Peculiarities of Mentor’s Competence of Pre-School and Pre-Primary Education Teaching Practice Organization and Reflection - Monkevičienė, Ona; Autukevičienė, Birutė (Pedagogika, 2013)
The aim of education is not only to echo wants of modern society, but also „to be a vanguard of democratizing society“. Hence education is closely related to the social cultural environment. The researcher of Lithuanian education and educational scientific development, Doctor of literature, actively participating in society life, an initiator and organizer of education reform documents, Dr. Meilė Lukšienė (1913–2009) announced pursuance: “it would be great if new school turned back at culture would become its home, where a young or old student could just exist. This existence itself would constantly enrich the person, would reach his or her soul, and would exhibit all person’s virtues”. One of the most important persons in educational institution is a pedagogue. Obviously, today‘s society raises higher and higher requirements. National strategy project of education 2013–2022 says that pedagogues must be reflecting, constantly perfecting themselves and working successfully. Such pedagogues will succeed in turning Lithuanian education into stable foundation for an independent and ambitious person who creates his future, the future of his country’s and the world’s future responsibly and solidarily. Therefore, high quality modern studies are necessary to provide a future pedagogue with deep theoretical knowledge, to create conditions for training practical pedagogue‘s skills of the highest level and to develop cultural awareness of a future pedagogue. M. Lukšienė (2000) stated that teacher training forms cannot be separated from contents. Seeking high quality studies, integrating theoretical knowledge into practice, an important role goes to mentoring. Regulation of teacher training (2012 May 15, ord, Nr. V-827) describes mentor as an experienced and successfully working pedagogue, trained according to the orders confirmed by Education and Science Ministry, who is a help to a student on teaching practice in one or several institutions or any other institutions (companies, organizations) related to pedagogical work in any way. Thus, a mentor must be able to create appropriate conditions for teaching practice, help a student realize practice programme and reflect upon gained experience. This makes the essence of mentor’s practice organization and reflection competence. The article draws great attention to the integration of theory and practice in the process of training teachers, which enables to recognize theoretical knowledge and to apply it in concrete practical situations, create the opportunity for future pedagogues to perfect their professional skills. The article also discusses models of organizing teaching practice, mentor’s role in instructing practice, the meaning and importance of mentor‘s professional practice organization and reflection competence from the point of view of experienced students. The main aim of the article research–to reveal pre-school and pre-primary mentor’s competence of professional practice organization and reflection, the importance and expression of its components while mentoring students’ practice.